Participatory Governance and Community-Based Research at Mass Culture - Dubuc, Laurence D. (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2023)
This article uses the national arts research network Mass Culture (MC) as a case study for assessing the strengths and limitations of participatory governance and community-based research for reimagining and enacting better futures in the Canadian arts sector. MC is currently the only digital network that takes such an approach to promote the equitable mobilization of arts research in Canada, which falls in line with broader trends and values associated with the participatory turn of cultural policy. At MC, this orientation is first reflected in the governance structure, which grew out of both grassroots processes and formal consultations involving key actors in the Canadian arts community. Here, I draw inspiration from Rosenau’s (Rosenau & Czempiel, 1992) definition of governance to refer to MC’s system of rule, which includes informal mechanisms such as intersubjective meanings, along with formally sanctioned regulations such as charters, terms of reference, etc. MC’s approach is also activated by the methods through which it designs, implements, and evaluates cross-sectoral collaborative projects at the national level. By experimenting with various community-engaged methods tailored to each of its initiatives, MC seeks to build the relational and data infrastructures that are needed to ensure that the research it produces is both relevant and easily accessible to potential users, from practitioners, artists, academics, arts funders, and policymakers, to those working at the intersection of several professional roles. By providing an in-depth account of MC’s emergence as a networked organization and by elaborating on its community-based approach to research, this article aims to contribute new knowledge about the value of various models of collaboration in the fields of cultural policy and cultural management.